2003
DOI: 10.1093/ndt/gfg450
|View full text |Cite
|
Sign up to set email alerts
|

The effect of frequent or occasional dialysis-associated hypotension on survival of patients on maintenance haemodialysis

Abstract: Mortality in patients with f-IDH is significantly higher than in those without such events. After adjustments for covariates, however, there is no independent effect of frequent or occasional episodes of IDH on mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
120
3
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(129 citation statements)
references
References 12 publications
3
120
3
2
Order By: Relevance
“…Some authors suggested that glaucoma patients with an exaggerated nocturnal reduction in systemic arterial pressure have an altered OPP outside the period of arterial pressure reduction, which is possibly related to a general vascular dysregulation (27) . In addition to a circadian rhythm for arterial pressure where we observe a nocturnal fall, we also have some situations during the HD session in which we see a reduction in the average arterial pressure value (4)(5) . Therefore, there is hypotension during the HD session.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Some authors suggested that glaucoma patients with an exaggerated nocturnal reduction in systemic arterial pressure have an altered OPP outside the period of arterial pressure reduction, which is possibly related to a general vascular dysregulation (27) . In addition to a circadian rhythm for arterial pressure where we observe a nocturnal fall, we also have some situations during the HD session in which we see a reduction in the average arterial pressure value (4)(5) . Therefore, there is hypotension during the HD session.…”
Section: Discussionmentioning
confidence: 82%
“…More serious complications include cardiac arrhythmia, convulsion, gaseous embolism, and intracranial hemorrhage (3) . Arterial hypotension still represents a major complication resulting from HD therapy; it frequently shortens the duration of dialysis and increases patient mortality rates (4)(5) . The pathogenesis of hemodynamic instability in response to fluid removal probably involves many factors such as defective plasma refilling (6) , abnormal body heating (7)(8) , an imbalance between endothelin and nitric oxide synthesis (9) , and defective adjustment of arteriovenous tone in response to the changes in the effective plasma volume (10) .…”
Section: Introductionmentioning
confidence: 99%
“…Stefánsson et al found patients with IDH to be younger, more likely to be male, and to have similar comorbid cardiovascular disease burdens to patients without IDH. By contrast, other studies found patients with IDH to be older, more likely to be female, and more likely to have cardiovascular comorbid conditions compared with patients without IDH (19,20). In addition, without time sequence data, we cannot exclude the possibility that therapeutic responses like blood flow reduction and early dialysis termination were initiated for reasons other than hemodynamic instability (e.g., faulty vascular access), potentially altering the associations.…”
mentioning
confidence: 83%
“…Furthermore, the authors did not account for several potential confounding variables including hemoglobin (21), albumin (19,20), and low predialysis BP (20,21). Although multivariable models included a variable for uncontrolled hypertension, defined as mean predialysis BP.140/90 or mean postdialysis BP.130/85, this dichotomous term does not account for the U-shaped association of BP and outcomes (22).…”
mentioning
confidence: 99%
“…Standard evaluation of overload is made as difference between actual and ideal weight ( "dry weight"); determination of the latter is still mostly based on clinical evaluation only [22], a method far too empiric that results in a difficult esteem of real overload severity and consequent potential harm during a too strict HD session, exposing patients to risks of intradialytic hypotension, i.e. increased mortality [23]. Moreover, use of blood pressure value measured at the time of HD session as marker of chronic volume overload severity has been questioned, as it may be heavily impaired by imprecision, and consequently represent only a very poor marker of volume overload [24].…”
Section: Dehydration During Hd Led To Reduction Of All Main Clinical mentioning
confidence: 99%